(untitled) (Bangladesh Journal of Child Health, 2012)
Background: Retinopathy of prematurity (ROP) is a retinal vascular disorder of preterm neonates resulting in visual impairement. Along with prematurity, very low birth weight and hyperoxia, role of blood transfusions in the occurrence of ROP has been strongly emphasized. Objective: To determine the relationship of timing and volume of blood transfusion and other factors with the development of ROP in preterm very low birth weight (VLBW) newborn infants. Methods: This was a prospective observational study. It was done among the premature (<34 weeks) VLBW neonates admitted to SCABU and ICU of Dhaka Shishu Hospital. Neonates who fulfilled the inclusion criteria were followed up daily to record certain clinical factors and effect of blood transfusions. Among 93 discharged neonates subjected to have ophthalmological screening, 58 (62%) completed the examinations. After ophthalmological study, they were divided into Normal group (n=35) that included newborns without ROP, and Abnormal group (n=23) that included newborns with ROP. Comparative analysis of recorded clinical factors was done between the two groups. Results: Blood transfusion during the first week of life (p=.002, OR 1.15; C.I. 1.01 1.32) and cumulative volume of transfused blood (ml/kg) (p=.002, OR2.8, CI: 1.65- 4.41) were significantly associated with the development of ROP. All neonates with ROP have got one or more transfusions (p=.003; OR 2.11 95% CI.012-.676). Univariate analysis demonstrated that VLBW (p=.03; OR .93; 95% CI=.87-.91), duration of oxygen inhalation (p=.001; OR 28; 95% CI 4.85-17.81) and mechanical ventilation (p= .001; OR3.36; 95% CI2.5-5.52) has significant relationship with ROP. Conclusion: This study showed that repeated blood transfusion resulting in large cumulative volume, transfusion in first week of life has significant association with ROP. Other risk factors are very low birth weight, prolonged oxygen inhalation and mechanical ventilation. DOI: http://dx.doi.org/10.3329/bjch.v34i2.10215 BJCH2010; 34(2): 38-43